The Legal and Public Health Implications Of Digital Health Technologies - Chandrakar, Ekta; Dahiya, Aman (South Eastern European Journal of Public Health, 2024)
To reduce the negative effects of digitization, normative advice in international human rights legislation incorporates digital health into ethical and human rights frameworks. The use of digital health technology for universal health coverage (UHC) is acknowledged to have benefits, but its implementation must be based on respect for human rights, equity, and ethics, as well as upholding norms of acceptable quality, safety, and morality. The WHA acknowledged the necessity to use digital health technologies in the wake of the COVID-19 pandemic in 2020, but stressed that in doing so, they must "pay particular attention to digital inclusion, patient empowerment, data privacy and security, legal and ethical issues, and the protection of personal data." This paper's goal is to critically assess the proposed legislative framework and policy that regulate digital health technologies in India, as well as the implementation of digital health.